Owner/managers' financing preferences and the proportion of firm's capital structure: evidence from successful SMEs in Malaysia - Mohamed Zabri, Shafie (2014)
The importance of economic contributions of Small and Medium-sized Enterprises (SMEs) around the world particularly in developing countries requires better understanding of financial practices among SMEs. This research investigates the financial practices among SMEs in Malaysia, within the list of Enterprise 50 award winners from 1998 to 2010. Focuses are on SME owner/managers' level of financing preferences towards available sources of financing and also its relationship with the proportion of the firm's capital structure. Electronic surveys were conducted with a response rate of 29.5%. SME managers are found to have a higher preference towards debt financing from banking institutions which is shown by the average debt{o-equity ratio among these SMEs of 57 to 43. Account payable and retained earnings were two types of liabilities with higher proportion in the firm's capital structure. Bivariate analysis reveals that owner/managers' preferences towards internal equity financing, external equity financing and debt financing were found to have a statistically significant relationship with the proportion of firms' short-term financing, long-term financing and also equity financing. This research enhances the existing body of knowledge of financial practices of SMEs, particularly within the context Malaysian SMEs by providing the information on manager's level of financing preferences and its relationship with the proportion of firm's capital structure.